Preliminaries - Blanco-Mesa, Fabio (Unidad Editorial UPTC, 2020)
Revista Inquietud Empresarial / Escuela de Administración de Empresas /Facultad de Ciencias Económicas y Administrativas Universidad Pedagógica y Tecnológica de Colombia. Tunja - Boyacá́ - Colombia Vol. 1 (2) (1988) - Vol. XIX (1) (2020). Tunja: UPTC., 1988 - 2020. Semestral ISSN 0121-1048 Printed, ISSN 2422-3220 Online Journal Inquietud Empresarial© belongs to Escuela de Administración de Empresas, Facultad de Ciencias Económicas y Administrativas Universidad Pedagógica y Tecnológica de Colombia. The publication rights of the articles that appear in each edition belong to the School of Business Administration of the Universidad Pedagógica y Tecnológica de Colombia. The reproduction and citation of the material contained in the journal are authorized, as long as it is explicitly indicated: name of the journal, name of the author(s), year, volume, number, and pages of the source article. The mention of products or commercial firms in the journal does not imply a recommendation or support by the University or the School; the use of such products must follow the recommendations of the labels. Published: 01/12/2020